(untitled) (diségno, 2022)
This article explores the role of drawing in relation to design, not so much as a specific creative act, capable of informing and representing design ideas, or as a ‘manifestation of the idea’ per se, but rather as a dense and sedimented knowledge that is increasingly relevant for interaction design – and extensively in any design project. Looking at examples such as video game interfaces and other everyday use artifacts, as well as theoretical reference models for the interaction design community (from Donald Norman’s to Paul Dourish’s, from Anthony Dunne and Fiona Raby’s to Branden Hookway’s, etc.), it is possible to bring out and discuss the centrality of the role of drawing in rethinking strategies of the interaction project, while considering the interface as a specific ‘place’ where not only the mediation between user and designed content takes place, but also that between drawing and design is activated. If windows, mirrors, and lenses can be considered as mediation devices of the visible, interfaces of digital devices can synthesize, make coexist and multiply their functioning and consequences, for example when they are meant to relate collections of data with their possible representations. Furthermore, recent discoveries in other fields, such as chemistry and biology, lead us to rethink together both drawing and design, starting from new epistemological models which extensively rely on the notion of interface.